Impact of Organizational Citizenship Behavior, Leadership, Individual Characteristics and Competence on Teacher Performance - Januar Adie Chandra; Ni Nyoman Putu Martini G; Nurul Qomariah (Universitas Muhammadiyah Jember, 2020)
The purpose of this study was to determine the effect of organizational citizenship behavior (OCB), leadership, individual characteristics and competence on the performance of teachers of SMK Swata in Bondowoso Regency. The population of this research is all employees who are in Private Vocational High Schools (SMKS) in all of Bondowoso Regency, totaling 975 Educators of Education Personnel (PTK). The number of samples of this study was 110, with a purposive sampling method. Validity and reliability tests were conducted to test the measuring instrument in the form of a questionnaire. The analysis technique used is WarpPLS 2.0. The results showed that organizational citizenship behavior had a positive effect on teacher performance, leadership had a positive effect on teacher performance, individual characteristics had no positive effect on teacher performance, competence had no positive effect on teacher performance.